2005
DOI: 10.1111/j.1440-1614.2005.01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of omega-3 fatty acids as a treatment for depression in the perinatal period

Abstract: There is a relative lack of knowledge about the safety of standard antidepressants in the perinatal period. There is a clear need for more research into alternative treatments, such as omega-3 fatty acids, in the management of depression in the perinatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…There was early enthusiasm for omega-3 fatty acids, although most randomized clinical trials to date have failed to show that the active treatment differs from placebo. (Freeman et al, 2006), (Rees, Austin, & Parker, 2005). However meta-analysis for the role of omega-3 fatty acids for maternal MD has been found to be less consistent and further definitive studies are needed (Hosli, Zanetti-Daellenbach, Holzgreve, & Lapaire, 2007) .…”
Section: Discussionmentioning
confidence: 99%
“…There was early enthusiasm for omega-3 fatty acids, although most randomized clinical trials to date have failed to show that the active treatment differs from placebo. (Freeman et al, 2006), (Rees, Austin, & Parker, 2005). However meta-analysis for the role of omega-3 fatty acids for maternal MD has been found to be less consistent and further definitive studies are needed (Hosli, Zanetti-Daellenbach, Holzgreve, & Lapaire, 2007) .…”
Section: Discussionmentioning
confidence: 99%
“…A 1% increase in plasma DHA was related to a 59% decrease in risk of depressive symptoms postpartum. 11 Unfortunately, as described earlier, pregnant women's diets are often deficient in DHA, which is unfortunate given fetuses' high need for it. As Rees et al 11 noted, during the last trimester of pregnancy, fetuses accumulate an average of 67 mg per day of DHA.…”
Section: Additional Effects Of Docosahexaenoic Acid In the Perinatal mentioning
confidence: 99%
“…Fish consumption has a similar effect on postpartum depression. Rees et al 11 observed that the rates for postpartum depression in North America and Europe are 10 times those in Taiwan, Japan, Hong Kong, and some regions of China. In a large cross-national ecologic analysis of 41 published studies with more than 14,532 women from 22 countries, 20 Hibbeln noted that postpartum depression was up to 50 times more common in countries with low fish consumption.…”
Section: Omega-3s and Depression In Population Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…43 The demonstrated correlation between lower gestational seafood consumption and higher rates of postpartum depression 44 suggests that individual v3FA indices may also be a determinant of postpartum mood status. 45,46 Possibly associated with the limited seafood intake in North America, the incidence of postpartum depression is in the range of 12% compared with about 2% in Japan where fish consumption is high 44 (although major cultural differences in the way the two societies are organised may also be important). Furthermore, low DHA in breast milk and maternal red cells, resulting from low gestational intake of EFAs, 47 are commonly found in women with postpartum depression.…”
Section: Maternal and Paediatric Benefits Of Omega-3 Fatty Acid Suffimentioning
confidence: 99%